2020
DOI: 10.1109/access.2020.3000788
|View full text |Cite
|
Sign up to set email alerts
|

Frontal EEG Asymmetry of Emotion for the Same Auditory Stimulus

Abstract: Emotions play an important role in human interaction and decision-making processes. Frontal asymmetry in brain activity is a promising neurophysiological indicator of emotion. Emotions are psychologically explained by the valence-arousal model, but as yet, frontal asymmetry has not been fully explained by this model. In this study, we explored frontal asymmetry of emotions based on the valence-arousal model using the same auditory stimulus. Changes in emotional states using self-report questionnaires were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 84 publications
1
25
0
Order By: Relevance
“…Figure 6 depicts the average neural pattern changes for fear vs. joy emotional states. In general, these pictures show that CSP filters appeared as generally smoother and physiologically more relevant, with strong weights in relevant brain regions, as expected from findings in the literature [26,32,33,45,46,65]. With respect to each of the considered paradigm, the findings are elaborated subsequently.…”
Section: Cortical Dynamics With Respect To Stimulus Paradigmssupporting
confidence: 70%
See 4 more Smart Citations
“…Figure 6 depicts the average neural pattern changes for fear vs. joy emotional states. In general, these pictures show that CSP filters appeared as generally smoother and physiologically more relevant, with strong weights in relevant brain regions, as expected from findings in the literature [26,32,33,45,46,65]. With respect to each of the considered paradigm, the findings are elaborated subsequently.…”
Section: Cortical Dynamics With Respect To Stimulus Paradigmssupporting
confidence: 70%
“…Often, within this domain, asymmetric frontal cortical activity is studied by comparing alpha oscillation responses across the left and right brain regions. Lee et al [26] reported a decrease in alpha power within the right and left frontal brain regions. Otten and Jonas [52] conducted a study to evoke emotions using emotion-evoking words, and compared pleasant, unpleasant, and neutral conditions.…”
Section: Alpha Bandmentioning
confidence: 98%
See 3 more Smart Citations